Interfaces Epistemological Approaches to Inter and Transdisciplinary in Revitalization of the Built Environment (Revista Brasileira Multidisciplinar, 2010)
Indiscriminate clandestine depositions of construction wastes have produced enormous and irreparable damage to the environment, causing pollution of public urban areas, shortening the landfills' life cycle, promoting sedimentation of sub-watersheds and burden on public coffers. The object of this study is the management to deal with demolition wastes using them on residential interventions of urban cluster. This study aims to show the epistemological interfaces in Interdisciplinary and Transdisciplinary approaches of the object of study proposed. Based on the epistemology and on the concepts of interdisciplinarity and transdisciplinarity, we'll seek to identify the disciplines and their interfaces with the object, offering a brief background on sustainability and economic development, materials, construction waste, social relations. Recycling construction waste can generate social inclusion programs by employing and training disqualified human resources as well as enabling automanagement.
Keywords: Interdisciplinarity; Transdisciplinarity; Sustainability; Construction waste; Environment.